THE ANALYSIS OF BANK FINANCIAL PERFORMANCE USING ALTMAN (Z-SCORE) TO PREDICT BANKRUPTCY (Study On Listing And Delisting Bank In Indonesian Stock Exchange) - Risa Widia Ariesta (Fakultas Ilmu Administrasi Universitas Brawijaya, 2015)
This research examines whether Altman (Z-Score) is suitable to measure the financial performance of listed and delisted banks in Indonesian Stock Exchange. Altman (Z-Score) is a method to predict a bankruptcy. The type of this research is descriptive research. This research is using documentation method as data collection method. The sampling method is purposive sampling. The samples of this research are consists of, eight listed banks and three delisted banks. There are assumptions about listed companies which have good financial performance, while delisted companies have poor financial performance. Delisting decision on Indonesian Stock Exchange can be caused by the bankruptcy. However, delisting decision is also based on the company decision to be going concern. The research results showed several listed banks were in gray area during observation. It indicated not all of listed banks have good financial performance. The results of Altman-test for delisted banks were in safe area. It indicated that not all delisted banks had poor financial performance. In fact, the reason of several companies to being delisted because of consolidation or expand its business. Keywords: Altman (Z-score), Bank, Listing, Delisting, Financial Performance